Effects of air pollution on clinical pregnancy rates after in vitro fertilisation (IVF): a retrospective cohort study. Issue 11 (29th November 2022) - Tartaglia, Marie; Chansel-Debordeaux, Lucie; Rondeau, Virginie; Hulin, Agnès; Levy, Alexandre; Jimenez, Clément; Bourquin, Patrick; Delva, Fleur; Papaxanthos-Roche, Aline
Abstract : Objective: To evaluate the effect of air pollution, from oocyte retrieval to embryo transfer, on the results of in vitro fertilisation (IVF) in terms of clinical pregnancy rates, at two fertility centres, from 2013 to 2019. Design: Exploratory retrospective cohort study. Setting: This retrospective cohort study was performed in the Reproductive Biology Department of Bordeaux University Hospital localised in Bordeaux, France and the Jean Villar Fertility Center localised in Bruges, France. Participants: This study included 10 763 IVF attempts occurring between January 2013 and December 2019, 2194 of which resulted in a clinical pregnancy. Primary and secondary outcome measures: The outcome of the IVF attempt was recorded as the presence or absence of a clinical pregnancy; exposure to air pollution was assessed by calculating the cumulative exposure of suspended particulate matter, fine particulate matter, black carbon, nitrogen dioxide and ozone (O3), over the period from oocyte retrieval to embryo transfer, together with secondary exposure due to the presence of the biomass boiler room, which was installed in 2016, close to the Bordeaux University Hospital laboratory. The association between air pollution and IVF outcome was evaluated by a random-effects logistic regression analysis. Results: We found negative associations between cumulative O3 exposure and clinical pregnancy rate (OR=0.92, 95% CI = (0.86 to 0.98)), and between biomass boiler room exposure and clinical pregnancy rate (OR=0.75, 95% CI = (0.61 to 0.91)), after adjustment for potential confounders. Conclusion: Air pollution could have a negative effect on assisted reproductive technology results and therefore precautions should be taken to minimise the impact of outdoor air on embryo culture.